Soil Physicochemical and Biological Properties of Paddy-Upland Rotation: A Review - Wei Zhou; Teng-Fei Lv; Yong Chen; Anthony P. Westby; Wan-Jun Ren (The Scientific World Journal)
Paddy-upland rotation is an unavoidable cropping system for Asia to meet the increasing demand for food. The reduction in grain yields has increased the research interest on the soil properties of rice-based cropping systems. Paddy-upland rotation fields are unique from other wetland or upland soils, because they are associated with frequent cycling between wetting and drying under anaerobic and aerobic conditions; such rotations affect the soil C and N cycles, make the chemical speciation and biological effectiveness of soil nutrient elements varied with seasons, increase the diversity of soil organisms, and make the soil physical properties more difficult to analyze. Consequently, maintaining or improving soil quality at a desirable level has become a complicated issue. Therefore, fully understanding the soil characteristics of paddy-upland rotation is necessary for the sustainable development of the system. In this paper, we offer helpful insight into the effect of rice-upland combinations on the soil chemical, physical, and biological properties, which could provide guidance for reasonable cultivation management measures and contribute to the improvement of soil quality and crop yield.